Evaluation of asphalt mixtures incorporating electric arc furnace steel slag and copper mine tailings for road construction - Oluwasola, Ebenezer Akin (Elsevier, 2015)
This study evaluates the suitability of using electric arc furnace (EAF) steel slag and copper mine tailings (CMT) as substitution for conventional aggregates used in pavements for roads and highways. Four mix designs containing EAF steel slag and CMT at different proportions were investigated. Mix 1 was 100% granite, Mix 2 consisted of 80% granite and 20% CMT, Mix 3 consisted of 80% EAF steel slag and 20% CMT while Mix 4 consisted of 40% granite, 40% EAF steel slag and 20% CMT. Marshall stability, moisture susceptibility, indirect tensile resilient modulus and dynamic creep tests were used to evaluate the laboratory performance of the mixtures. The findings reveal that substituting natural granite aggregates with CMT and EAF steel slag improved the performance properties of asphalt mixtures. The mixture containing 80% EAF steel slag and 20% CMT produced the best results. The resilient modulus results show that the resilient modulus of the mixes decreased as the temperature increased. Also, the aging process significantly increased the resilient modulus and dynamic creep modulus values. Thus, the study has revealed that the mining by-products (CMT) and metallurgical by-products (EAF steel slag) can be utilized as aggregates in road construction.